2015
DOI: 10.1080/01635581.2015.1019639
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carbohydrate and Prostate Cancer Risk: A Meta-Analysis

Abstract: Carbohydrate intake has been inconsistently associated with risk of prostate cancer. We review and quantitatively summarize the evidence from observational studies in a meta-analysis. We searched the PubMed database for observational studies related to the association of carbohydrate intake and prostate cancer risk up to December 25, 2013. Summary relative risks (RRs) were estimated by the use of a random effects model. We included 13 case-control studies with 4,367 cases and 6,205 controls, and 5 cohort studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(110 reference statements)
4
3
0
Order By: Relevance
“…All included studies ascertained outcomes according to histologic findings. A recent meta-analysis reported that there was no clear association between carbohydrate intake and the risk of prostate cancer, 48 which was in accordance with our study. However, we evaluated as many as five factors, including dietary fiber, whole grains, carbohydrate, GI, and GL.…”
Section: Discussionsupporting
confidence: 93%
“…All included studies ascertained outcomes according to histologic findings. A recent meta-analysis reported that there was no clear association between carbohydrate intake and the risk of prostate cancer, 48 which was in accordance with our study. However, we evaluated as many as five factors, including dietary fiber, whole grains, carbohydrate, GI, and GL.…”
Section: Discussionsupporting
confidence: 93%
“…Null findings for dietary carbohydrates, GI and GL in relation to adiposity-related cancers are consistent with the literature, as most studies on this topic report null or weak associations ( 17 20 , 35 , 36 ) . Evidence on carbohydrate food sources in relation to cancer risk is limited.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, Drake et al reported that the lowest consumption of monosaccharides corresponded with a 31% decreased risk of symptomatic prostate cancer (i.e., exhibiting lower urinary tract or other malignancy-related symptoms) [37]. Another meta-analysis by Zhai and colleagues found no significant associations between total carbohydrate intake and PCa risk, even when stratifying by study design (case-control and cohort) [38]. These findings were further substantiated by Fan et al who failed to report significant associations between dietary carbohydrate consumption and risk of advanced and non-advanced PCa on data from 22 studies that included 6 prospective cohort and 16 case-control designs [39•].…”
Section: Primary Prevention Of Cancer: Simple Carbohydratesmentioning
confidence: 99%